109k views
3 votes
Question 10 of 10 What is the recursive formula for the geometric sequence with this explicit formula? •(-3) la = 9 O A. OA, an ar-1 0 la = -9 = O B. an = an-1 . im 3 OC. 3 a = an-1 • (-9) (2, - - 1/2 a 3

Question 10 of 10 What is the recursive formula for the geometric sequence with this-example-1
Question 10 of 10 What is the recursive formula for the geometric sequence with this-example-1
Question 10 of 10 What is the recursive formula for the geometric sequence with this-example-2
User Bers
by
5.7k points

1 Answer

6 votes

Given the explicit formula for the Geometric Sequence:


a_n=9\cdot(-(1)/(3))^((n-1))

Where the nth term is:


a_n

Then, you need to remember that, by definition, the Recursive Formula for a Geometric Sequence has this form:


a_n=a_(n-1)\cdot r

Where "r" is the common ratio.

In this case, having the explicit formula with the form:


a_n=a_1\cdot r^((n-1))

You can identify that:


r=-(1)/(3)
a_1=9

Therefore, you can set up the following recursive formula:


a_n=a_(n-1)(-(1)/(3))

Hence, you get:


\begin{cases}a_1=9_{} \\ \\ a_n=a_(n-1)(-(1)/(3))\end{cases}

Therefore, the answer is: Option A.

User Jiexishede
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.